Resilience in J.S. Khairen’s Novel Dompet Ayah Sepatu Ibu: A Study of Max Weber’s Social Action - Khurun'in Rizki Az Zahra; Titik Indarti (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Resilience is defined as an individual's psychological ability to adapt, survive, and bounce back from difficult situations, trauma, or significant stress. It's not just about surviving, but also about the process of recovery and becoming stronger after facing adversity. Resilient people are able to manage their emotions and remain productive. In Max Weber's perspective, social action is defined as behavior oriented towards certain goals, whether driven by individual or collective interests. This theory encompasses four main concepts, namely instrumental rationality, value rationality, traditional, and affective action. This study aims to describe the forms of resilience in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen using Max Weber's theory of social action. This study uses a qualitative descriptive method with a sociological literary approach. The research data comes from the novel Dompet Ayah Sepatu Ibu (2023) in the form of quotations that represent the resilience of the characters' social actions in an effort to break structural poverty. The research data were collected through reading and note-taking techniques using non-test instruments, namely observation guidelines. The research data were analyzed using objective hermeneutics. The results of the study indicate the existence of forms of resilience in Max Weber's four types of social action: instrumental rationality resilience, value rationality resilience, traditional action resilience, and affective action resilience, which are causally interrelated. The research conclusion confirms that these four forms of action are the basis for the resilience of the characters in the novel.